PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 012 PARIT KARTO SUNGAI SEGAJAH KEC. KUBU KAB. ROHIL - Sudirman Sudirman; Hendri Marhadi; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was motivated by the percentage of students who achieve KKM 70 in the first semester of 2015-2016 are still low. Of the 19 students were only 8 people (42.11%) students who achieve KKM and 11 people (57.89%) students who have not reached the KKM with an average grade 59.47. This is because teachers rarely use learning models during the learning process in the classroom. From the problems of classroom action research needs to be done by applying problem-based learning model. Place of research is in SD Negeri 012 Segajah Sungai Parit Karto Kec.Kubu with research subjects are students of fourth grade totaling 19 people, male students and 10 female students 9. This study was conducted in two cycles. Instruments of data collection in this study is the observation sheet teacher activity, student activity sheets observation and tests daily tests. Observations show that the activities of teachers and students has increased. Activities of teachers, in the first cycle 71.59% increase in cycle II to 84.08% with an increase of 12.49%. For student activities, in the first cycle and a 64.77% increase in the second cycle into 81.81% with an increase of 17.04%. Student learning outcomes in basic score with an average of 54.47 in the first cycle increased to 77.11 in the second cycle increased to 84.74. Increase in the average score of the first cycle of basic to 17.63 and from the first cycle to the second cycle increased by 7.63. The percentage increase in student learning outcomes as a whole amounted to 39.54%. Mastery learning students on a base score of 19 students showed that as many as 8 students (42.11%) reached the KKM has been set, the first cycle increased to 16 students (84,21%), on the second cycle increased to 18 students (94.74). The increase of the basic score the first cycle to 29.65% and from the first cycle to the second cycle increased by 9.90%. From the above shows that through the implementation of Problem Based Learning Model to improve learning outcomes mathematics Elementary School fourth grade students 012 Sungai Parit Karto Segajah Kec.Kubu in academic year 2015/2016. Keywords: Problem Based Learning Model, Math Learning Outcomes